Correction: Catalytic synthesis of distillate-range ethers and olefins from ethanol through Guerbet coupling and etherification. Issue 18 (27th August 2019) - Eagan, Nathaniel M.; Moore, Benjamin M.; McClelland, Daniel J.; Wittrig, Ashley M.; Canales, Emmanuel; Lanci, Michael P.; Huber, George W.
Abstract : Correction for 'Catalytic synthesis of distillate-range ethers and olefins from ethanol through Guerbet coupling and etherification' by Nathaniel M. Eagan et al., Green Chem., 2019, 21, 3300–3318.